PENGARUH WAKTU PEMANASAN PADA PROSES DEASETILASI TERHADAP YIELD CHITOSAN DARI LIMBAH KULIT UDANG SEBAGAI ALTERNATIF BAHAN PENGAWET MAKANAN - Budhi .; Satiani . (Program Studi Teknik Kimia, Universitas Pamulang, 2017)
The solution can be reached from the alternative preservatives are not expensive is using waste from organic materials. An example is chitosan from crab shell waste or waste shrimp shells. Chitosan has a high economic value. So that it can provide benefits to producers or sellers of food and also provide security to the people of the food they will consume. This research aimed to study the effect of heating time in the process of deacetylation, the yield chitosan from shrimp shell waste as an alternative preservatives. Shrimp shell waste is cleaned first, and then sieved with a 120 mesh size filter. After it was weighed, added a solution of NaOH (deproteination process) comprising water reacted with NaOH and then heated at 100 ° C for 2 hours and then filtered, after which the precipitate obtained is drained. Dried precipitate was added HCl (demineralization), then heated to a temperature of 80 ° C for 8 hours, then filtered and after the precipitate obtained (chitin) is dried. Chitin is reacted with NaOH (deacetylation) and then heated at 80 ° C with a variety of heating time 2 hours, 3 hours, 4 hours, 5 hours and 6 hours, and then filtered. The research showed the optimum heating time is 4 hours at 80 ° C at a yield of 23.08% chitosan.Keywords : chitosan, deacetylation, deproteination, preservatives, yield